The causes of the English teachers’ problems on professional competence at Vocational High School - Syamsinar; Khaeruddin (Center for Humanities and Innovation Studies, 2018)
The objectives of this research aimed at finding out the causes of the problems in teaching English and the possible solution toward the problems of the teachers in teaching English subject at vocational high schools. The researcher applied the purposive sampling technique in selecting the participants. The participants consisted of two advanced teachers and two beginner teachers at vocational high schools in Somba Opu sub-district. The additional participants were two headmasters that focused on the possible solution for dealing with the problem found by the English teachers at VHS. This research used a descriptive approach and qualitative method. The data collected using two instruments namely semi-structured interview and observation checklist. The data analyzed by using the framework of Miles and Huberman. The results of this research revealed nine causes of the problems on the professional competence of English teachers in teaching at vocational high school and the possible solution toward the causes. The outline of the causes of the problems on professional competence are the less effort of the English teachers to improve the linguistic aspects, lack of English for Specific Purpose knowledge, less of communicative competence, less preparation of teaching contents, less in using ICT as a teaching method and lack in managing the time and managing the class. The possible solution found in this research that the English teachers at VHS have to consider the students’ need, prepare the teaching planning and involved in the teaching training. Thus, this research recommends the government and the Educational trainer to facilitate the English teachers at VHS with education training of ESP knowledge and supporting the teachers in developing their professional competence.